Comparison of Dexmedetomidine and Clonidine as Adjuvants to Local Anesthetic in Brachial Plexus Blocks: A Systematic Review - Wijaya, Fanny; Hilda (International Medical Journal Corp. Ltd, 2024)
Introduction: Brachial Plexus Blocks (BPBs) use lignocaine and bupivacaine for anesthesia in upper limb surgeries, with adjuvants like clonidine and dexmedetomidine enhancing efficacy by increasing analgesia duration and reducing adverse events. This systematic review compares the efficacy and safety of dexmedetomidine versus clonidine as adjuvants in BPBs, explores sources of heterogeneity, and assesses evidence quality for sensory, motor, and analgesic outcomes. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Results: six publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Moderate to high-quality evidence suggests that dexmedetomidine is a more efficacious adjuvant to local anesthetics in BPBs compared to clonidine.